A FEM based methodology to simulate multiple crack propagation in friction stir welds. (15th October 2017) - Lepore, Marcello; Carlone, Pierpaolo; Berto, Filippo; Sonne, Mads R.
Highlights: A FEM based methodology for the simulation of multiple crack propagation is presented. Residual stresses are calculated starting from a cracked but virtually continuous component. The procedure was validated by comparison with a FEM-DBEM approach. Abstract: In this work a numerical procedure, based on a finite element approach, is proposed to simulate multiple three-dimensional crack propagation in a welded structure. Cracks are introduced in a friction stir welded AA2024-T3 butt joint, affected by a process-induced residual stress scenario. The residual stress field was inferred by a thermo-mechanical FEM simulation of the process, considering temperature dependent elastic-plastic material properties, material softening and isotropic hardening. Afterwards, cracks introduced in the selected location of FEM computational domain allow stress redistribution and fatigue crack growth. The proposed approach has been validated by comparison with numerical outcomes provided by a consolidated FEM-DBEM procedure, available in literature. The discussed procedures are substantially equivalent in terms of SIFs evaluation along the crack front at the cracks insertion, as well as with respect to crack sizes measured in three different points for each propagation step. This FEM-based approach simulates the fatigue crack propagation by considering accurately the residual stress field generated by plastic deformations imposed on a structural component and has general validity.